2005
DOI: 10.1073/pnas.0407443102
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-binding protein-1 (IGFBP-1) mediates hypoxia-induced embryonic growth and developmental retardation

Abstract: Although reduced fetal growth in response to hypoxia has been appreciated for decades, we have a poor understanding of the effects of hypoxia on embryonic development and the underlying cellular and molecular mechanisms. Here we show that hypoxia treatment not only resulted in embryonic growth retardation but also caused significant delay in developmental zebrafish ͉ heart development ͉ craniofacial skeleton ͉ morphogenesis ͉ oxygen H ypoxic stress causes major metabolic changes in all organisms requiring oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
160
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(173 citation statements)
references
References 58 publications
(55 reference statements)
11
160
2
Order By: Relevance
“…It is still unknown which mechanisms in the human fetus increase total and Np-IGFBP-1, although some have been suggested (37)(38)(39). IGFBP-1 concentrations in cord serum may be increased in FGR (10), as we confirmed.…”
Section: Discussionsupporting
confidence: 76%
“…It is still unknown which mechanisms in the human fetus increase total and Np-IGFBP-1, although some have been suggested (37)(38)(39). IGFBP-1 concentrations in cord serum may be increased in FGR (10), as we confirmed.…”
Section: Discussionsupporting
confidence: 76%
“…Igfbp1a is a secreted protein and can bind to insulin-like growth factors in extracellular environment with high affinity and thus inhibit their grow-promoting activity. 23,24 A previous study demonstrated that overexpression of igfbp1a caused growth and developmental retardation in zebrafish embryos. 24 Slc38a4 is an amino acid transporter and was suggested to be involved in the control of embryogenic growth in vertebrates by regulating the transport of amino acid.…”
Section: ■ Discussionmentioning
confidence: 99%
“…23,24 A previous study demonstrated that overexpression of igfbp1a caused growth and developmental retardation in zebrafish embryos. 24 Slc38a4 is an amino acid transporter and was suggested to be involved in the control of embryogenic growth in vertebrates by regulating the transport of amino acid. 25−27 A previous study reported that the down-regulation of slc38a4 was positively associated with postnatal growth deceleration in mice.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Indeed, IGFBP-1 levels and mRNA expression are markedly elevated in the umbilical cord blood of babies with profound and prolonged hypoxia, which is considered a leading cause of IUGR (72). In a recent study, the key role of IGFBP-1 in mediating the effects of hypoxia on fetal growth was confirmed in zebrafish, suggesting this is a conserved physiological mechanism to restrict IGFstimulated growth under hypoxic conditions (73).…”
Section: Regulation Of Gh Secretionmentioning
confidence: 97%